(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This article explores the importance and application of modern pedagogical technologies in the process of preparing young athletes for wrestling. The article analyzes in detail the concept of pedagogical technologies, their role in the physical, technical, tactical and psychological training of athletes. The effectiveness of the practical implementation of modern methods such as multimedia tools, individual approach, active training methods and test-monitoring has also been demonstrated.